Design of dynamic plant model and model-based controller for a heat recovery system with a swirling flow incinerator. (15th March 2018) - Cho, Jaeyoung; Kim, Yongtae; Song, Jeongwoo; Lee, Tae Kyung; Song, Han Ho
Abstract: We developed a plant model and model-based controller for a heat recovery system with a swirling flow incinerator located in South Korea. First, a plant model was designed to understand the dynamic characteristics of the system. The system was divided into three parts: incinerator, boiler, and steam drum. Then, each part was modeled with a multi-zone, zero-dimensional modeling scheme. Consequently, we found that the plant model followed the dynamic behavior of the target system, particularly for the seven important variables: boiler inlet temperature, superheater inlet temperature, boiler outlet temperature, oxygen mole fraction, steam production rate, steam pressure, and steam temperature. Then, we designed a multi-input multi-output controller for the system with a nonlinear control model. In the controller design, input variables were selected as air flow rate, fuel supply rate and steam valve opening area; while output variables were oxygen mole fraction of exhaust gas, steam production rate and steam pressure. A nonlinear control model was constructed by reducing the plant model. Then a linear quadratic regulator was applied while evaluating control gain at each time step. Finally, we validated the controller on the plant model, which adequately suppressed the disturbance on fuel composition and adjusted the steam production rate. Highlights: Plant model was built to simulate heat recovery system with a waste incinerator. Multi-input multi-output controller was designed for the system. The controller could efficiently suppress disturbance and adjusts load variation.